2012
DOI: 10.1155/2012/851810
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Determinants of Antiretroviral Drug Adherence among Nigerian Pregnant Women

Abstract: Background. The need for a high level of adherence to antiretroviral drugs has remained a major hurdle to achieving maximal benefit from its use in pregnancy. This study was designed to determine the level of adherence and identify factors that influence adherence during pregnancy. Method. This is a cross-sectional study utilizing a semistructured questionnaire. Bivariate and multiple logistic regression models were used to determine factors independently associated with good drug adherence during pregnancy. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
90
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 10 publications
13
90
7
Order By: Relevance
“…Unlike to study in Nigeria [15], male involvement in PMTCT care and support in this study was higher. This could be attribuTable to the integrated community interventions including PMTCT services in Ethiopia through the aid of Health Extension Program.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike to study in Nigeria [15], male involvement in PMTCT care and support in this study was higher. This could be attribuTable to the integrated community interventions including PMTCT services in Ethiopia through the aid of Health Extension Program.…”
Section: Discussioncontrasting
confidence: 99%
“…This is higher than study reported in Nigeria (80.6%), Zambia (82.5%) and Malawi (72.5%) [8,9,17]. This might be due to good practice of PMTCT and awareness of the participants in the study area and having good regular follow up that increase the adherence rate in the study area.…”
Section: Discussioncontrasting
confidence: 62%
“…A three month study in Nigeria among pregnant women revealed that adherence rate was 80.6% up on using 3 day recall method, with a non-adherent rate of 19.4% [8]. A retrospective cohort study in Malawi showed that the retention rate was 72.5% [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that even though maternal desire to protect their unborn child was the greatest adherence motivator for some, majority of these women missed their drugs nor partake in any other HIV-related services because of stigmatization and discrimination associated to being identified as HIV positive. These women had higher tendencies of self-stigmatization and were less aware that antiretroviral drugs help to increase their quality of life (Ekama, 2012). …”
Section: Discussionmentioning
confidence: 99%